2020
DOI: 10.1093/cid/ciaa1403
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Incident Diabetes Mellitus, Weight Gain, and Their Relationships With Integrase Inhibitor–Based Initial Antiretroviral Therapy Among Persons With Human Immunodeficiency Virus in the United States and Canada

Abstract: Background Integrase strand transfer inhibitor (INSTI)–based combination antiretroviral therapy (cART) is associated with greater weight gain among persons with human immunodeficiency virus (HIV), though metabolic consequences, such as diabetes mellitus (DM), are unclear. We examined the impact of initial cART regimen and weight on incident DM in a large North American HIV cohort (NA-ACCORD). Methods cART-naive adults (≥18 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
71
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 36 publications
3
71
1
Order By: Relevance
“…The association between INSTI and diabetes was attenuated by accounting for 12-month weight gain. Initiating combination ART regimens with INSTIs or PIs + NNRTIs may confer a greater risk of diabetes; this is probably mediated by weight gain (196). In the French DAT'AIDS study, 265 of the 19,462 HIV-infected patients initiating ART developed diabetes.…”
Section: Insulin Resistance and Diabetesmentioning
confidence: 99%
“…The association between INSTI and diabetes was attenuated by accounting for 12-month weight gain. Initiating combination ART regimens with INSTIs or PIs + NNRTIs may confer a greater risk of diabetes; this is probably mediated by weight gain (196). In the French DAT'AIDS study, 265 of the 19,462 HIV-infected patients initiating ART developed diabetes.…”
Section: Insulin Resistance and Diabetesmentioning
confidence: 99%
“…Although early ART regimens were associated with dyslipidemia and other metabolic derangements, contemporary ART, including the integrase strand transfer inhibitor (INSTI) class, are thought to have a better safety profile. Recent data has suggested that INSTI use may be associated with weight gain and the development of insulin-resistant diabetes [ 2 , 3 ] and, in rarer cases, accelerated hyperglycemia [ 4–6 ]. Bictegravir (BIC) is a second-generation INSTI, available in coformulation with emtricitabine (FTC) and tenofovir alafenamide (TAF), and is currently recommended as a first-line ART regimen for newly diagnosed PWH [ 7 , 8 ].…”
mentioning
confidence: 99%
“…The median duration of exposure for PLHIV who had ever received INSTIs was shorter than for those on PIs. Data from a large North American HIV cohort suggested that initiation of first cART regimens with INSTIs versus NNRTIs may confer an increased risk of incident diabetes, likely mediated through weight gain [ 46 ]. Studies have found weight gain following a switch to INSTIs, with more pronounced increases in HIV-positive women and with the use of dolutegravir [ 47 52 ].…”
Section: Discussionmentioning
confidence: 99%